Interleukin-12 (IL-12p70) Promotes Induction of Highly Potent Th1-Like CD4+CD25+ T Regulatory Cells That Inhibit Allograft Rejection in Unmodified Recipients - Verma, Nirupama Darshan; Hall, Bruce Milne; Plain, Karren Michelle; Robinson, Catherine M.; Boyd, Rochelle; Tran, Giang T.; Wang, Chuanmin; Bishop, G. Alex; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2014)
In rat models, CD4+CD25+T regulatory cells (Treg) play a key role in the induction and maintenance of antigen specific transplant tolerance, especially in DA rats with PVG cardiac allografts(1, 2). We have previously described generation of alloantigen specific Treg (Ts1), by culture of naïve natural CD4+CD25+ Treg (nTreg) with specific alloantigen and IL-2 for 4 days. These cells express mRNA for IFN-γ receptor (ifngr) and suppress donor but not third party cardiac allograft rejection mediated by alloreactive CD4+T cells at ratios of < 1:10. Here, we show that Ts1 also expressed the IL-12p70 specific receptor (il-12rβ2) and that rIL-12p70 can induce their proliferation. Ts1 cells re-cultured with rIL-12p70 alone or rIL-12p70 and rIL-2, suppressed proliferation of CD4+T cells in MLC at < 1:1024, whereas Ts1 cells re-cultured with rIL-2 and alloantigen only suppressed at 1:32-64. The rIL-12p70 alloactivated Ts1 cells markedly delayed PVG, but not third party Lewis, cardiac allograft rejection in normal DA recipients. Ts1 cells re-cultured for 4 days with rIL-12p70 alone, but not those re-cultured with rIL-12p70 and rIL-2, expressed more il-12rβ2, t-bet and ifn-γ, and continued to express the markers of Ts1 cells, foxp3, ifngr and il5 indicating Th1-like Treg were induced. Ts1 cells re-cultured with rIL-2 and alloantigen remained of the Ts1 phenotype and did not suppress cardiac graft rejection in normal DA rats. We induced highly suppressive Th1-like Treg from naïve nTreg in 7 days by culture with alloantigen, first with rIL-2 then with rIL-12p70. These Th1-like Treg delayed specific-donor allograft rejection demonstrating therapeutic potential